Economic Development of the Latin American Integration Association: Trends and Prospects - M. N. Tolmachev; E. V. Nikiforova; A. P. Tsypin (Статистика и экономика, 2021)
Relevance. Catch-up countries are at a disadvantage in the world economy and are forced to fight for world market share. For this purpose, they form political and economic alliances and associations designed to counter the aggressive policies of the developed countries. All this applies fully to countries that are members of the Latin American Integration Association (LAIA). In our opinion, the assessment of the position of the participating countries on the geopolitical map of the world deserves special attention.Purpose of the study consists in the formation of an author’s methodology for studying the economic development of countries that are members of the Latin American Integration Association and building a forecast in the medium term on the basis of statistical tools. Materials and methods. The study used general research methods, such as analysis, comparisons, historical, as well as mathematical and statistical, in particular tabular and graphical, descriptive statistics and elements of correlation-regression analysis. A set of these methods and algorithms made it possible to identify the patterns that have developed at the moment in the economies of the Latin American Integration Association countries, assess their positions regarding world leaders, and also build short-term development forecasts.Results. With considerable resources, the countries of the Latin American Integration Association have not been able to significantly increase the share of world GDP during the existence of the association, which throughout the period does not exceed 5%. Within the association, there is a considerable differentiation. So the dominant positions are occupied by Brazil, Mexico, Argentina, while the positions of outsiders, by a significant margin, are occupied by Uruguay, Ecuador and Cuba. The structure of the economies of the association countries is largely different from the developed countries: the former are dominated by manufacturing, while the latter are dominated by services. A causal analysis of the impact of industries on GDP per capita, conducted in two time slices in 1990 and 2019, showed that during this time the countries that are members of the association have not been able to reformat the structure of their economies, which does not allow successful competition with developed countries. An element of the scientific novelty of the study is the formation of a theoretical and methodological approach to the study of the economic development of the geopolitical structure, which is the Latin American Integration Association, as well as the testing of this approach based on the actual data of international organizations.Conclusion. The testing of the author’s methodology aimed at studying the economic development of LAIA member countries allows us to argue about the operability of the algorithm, which made it possible to establish the low efficiency of the integration policy of Latin American countries, which, despite the significant level of national wealth, does not allow us to form a trend towards economic growth, a decrease in dependence on the export of natural capital, and an increase in the standard of living of the population. Some research findings from the study can be used in training activities for the disciplines of “Macroeconomics”, “International Statistics”, “Geoeconomics”, “Econometrics”, as well as in the analysis of the joint dynamics of political and economic communities, associations and groups. In subsequent publications, an in-depth analysis of the causes of the economic decline in each member country of the association will be carried out, dominant factors affecting growth and GDP decline will be identified.